Usefulness of morphological characteristics for DUS testing of jute (Corchorus olitorius L. and C. capsularis L.) - Begum, T.; Kumar, D. (Spanish Journal of Agricultural Research, 2011)
Thirty two jute (Corchorus olitorius and C. capsularis) varieties, including 25 released/notified and seven of common knowledge, were characterized through distinctness, uniformity and stability (DUS) testing trials for two consecutive years using 17 heritable morphological traits prescribed in the Revised Official DUS Test Guidelines of Jute to enable identification of these varieties and for unambiguous ascertainment of distinctness. Out of 17 traits, 8 were found to be monomorphic, 7 dimorphic and only 2 polymorphic in C. capsularis, while 8 traits were dimorphic and 9 polymorphic among C. olitorius varieties, indicating their potential for varietal characterization. On the basis of this study no single character could identify all the varieties individually; however, when used in combination, identity and distinctness of almost all the C. olitorius varieties and 10 varieties of C. capsularis (Padma, JRC-212, Bidhan Pat-2, D-154, KTC-1, KC-1, JRC-80, Bidhan Pat-3, JRC-7447 and JRC-698) could be established individually. The remaining varieties of C. capsularis could be classified into two groups: early flowering group (JRC-321, UPC-94) and fine fibre group (JRC-4444, Bidhan Pat-1). Hence, morphological characters alone may not suffice for DUS testing of C. capsularis varieties. All the varieties of both species released in India so far albeit professed their uniformity and stability through morphological characterization, but use of biochemical and/or molecular markers along with search for other morphological traits need to be explored for the delineation of C. capsularis varieties.